Research and design of hybrid scheduling system of node operating system for cyber physical systems - Xiao-zhou DU; Chen-hong CAO; Jian-zhong QIAO; Shu-kuan LIN (Tongxin xuebao)
In accordance with the new characteristics of physical,internet and intelligence of CPS,a hybrid scheduling system was designed for CPS node operating system with real-time performance,flexibility,and adaptability.Based on the in-depth study of the intrinsic differences between event-driven scheduling mechanism and multithreaded one,a hybrid programming model was designed that combines collaborative multithread and hybrid stack management using adapter mechanism.A hybrid scheduling model was also designed that supports both event and thread task types.Reasonable real-time algorithms were implemented for verification.Experimental results show that the real-time per-formance of the scheduling system is obviously better than that of TinyOS,thus it is better suited for CPS than TinyOS does.